Perceiving numbers does not cause automatic shifts of spatial attention. (December 2015) - Fattorini, Enrico; Pinto, Mario; Rotondaro, Francesca; Doricchi, Fabrizio
Abstract: It is frequently assumed that the brain codes number magnitudes according to an inherent left-to-right spatial organization. In support of this hypothesis it has been reported that in humans, perceiving small numbers induces automatic shifts of attention toward the left side of space whereas perceiving large numbers automatically shifts attention to the right side of space (i.e., Attentional SNARC: Att-SNARC; Fischer, Castel, Dodd, & Pratt, 2003). Nonetheless, the Att-SNARC has been often not replicated and its reliability never tested. To ascertain whether the mere perception of numbers causes shifts of spatial attention or whether number–space interaction takes place at a different stage of cognitive processing, we re-assessed the consistency and reliability of the Att-SNARC and investigated its role in the production of SNARC effects in Parity Judgement (PJ) and Magnitude Comparison (MC) tasks. In a first study in 60 participants, we found no Att-SNARC, despite finding strong PJ- and MC-SNARC effects. No correlation was present between the Att-SNARC and the SNARC. Split-half tests showed no reliability of the Att-SNARC and high reliability of the PJ- and MC-SNARC. In a second study, we re-assessed the Att-SNARC and tested its direct influence on a MC-SNARC task with laterally presented targets. No Att-SNARC and no influence of the Att-SNARC on the MC-SNARC were found. Also in this case, the SNARC was reliable whereas the Att-SNARC task was not. Finally, in a third study we observed a significant Att-SNARC when participants were asked to recall the position occupied on a ruler by the numbers presented in each trial: however the Att-SNARC task was not reliable. These results show that perceiving numbers does not cause automatic shifts of spatial attention and that whenever present, these shifts do not modulate the SNARC. The same results suggest that numbers have no inherent mental left-to-right organization and that, whenever present, this organization can have both response-related and strategically driven memory-related origins. Nonetheless, response-related factors generate more reliable and stable spatial representations of numbers.